(untitled) (Baghdad Science Journal, 2012)
This study was conducted to determine the role of Phoenix dactylifera pollen grains suspension in improving reproductive efficiency of white male rats. In thisexperiment 40 adult male rats were divided randomly into five equal groups and by following oral administration:the first group was given Phoenix d. pollen grains suspension with concentration 18 mg/kg body weight daily, the second group was given 54 mg/kg, the third group was given 108 mg/kg and fourth group 216 mg/kg body weight, and the last group which represented a control group administrated distilled water only, the administration continued for 40 consecutive days. The effect of Phoenix d. pollen grains in reproductive efficiency was evaluated depending on some parameters such as: weights of (testes, epididymes, seminal vesicle and prostate gland), Some testes parameters of epididymis sperms (sperms concentration, percentage of both sperms motility and viability and percentage of normal sperms).and measuring of some hormonal levels which affect on spermatogenesis like [Luteinizing hormone(LH), Follicle stimulating hormone(FSH) and Testosterone hormone(T)]. The results showed a significant increase (P